Potential approaches to combat COVID-19: a mini-review - Sarwar, Zainab (Mol Biol Rep, 2020)
The outbreak of a novel coronavirus namely SARS-CoV-2, which first emerged from Wuhan, China, has wreaked havoc not only in China but the whole world that now has been engulfed in its wrath. In a short lapse of time, this virus was successful in spreading at a blistering pace throughout the globe, hence raising the flag of pandemic status. The mounting number of deaths with each elapsing day has summoned researchers from all around the world to play their part in driving this SARS-CoV-2 pandemic to an end. As of now, multiple research teams are immersed in either scrutinizing various antiviral drugs for their efficacy or developing different types of vaccines that will be capable of providing long-term immunity against this deadly virus. The mini-review sheds light on the possible approaches that can be undertaken to curb the COVID-19 spread. Possible strategies comprise viral vector-based, nucleic acid-based, protein-based, inactivated and weakened virus vaccines; COVID-19 vaccine being developed by deploying Hyleukin-7 technology; plant-based chimeric protein and subunit vaccines; humanized nano-bodies and human antibodies; intravenous immunoglobulin (IVIG) infusion therapy; inhibitors for ACE-2, Angiotensin 1 receptor (AT1R), complement system, viral proteins, host cell protease and endocytosis; shield immunity; IL-6R, NKG2A and hACE2-SARS-CoV-2-RBD interaction blocking monoclonal antibodies; SARS-CoV RdRp-based drugs, traditional Chinese medicine, repositioned and anti-viral drugs. These vaccines and drugs are currently being screened in the clinical trials as several of them have manifested positive results, hence increasing the probability of becoming one of the potential treatments for this disease.